(untitled) (Research, Society and Development, 2022)
Plagiarism of academic works is a topic that is still little discussed, showing that the indiscriminate use of the internet can promote possible undue copies with incursion into copyright, even in an unintentional way. The present work aims, through a descriptive literature review and a qualitative approach, to analyze, describe and compare 15 plagiarism verification and detection tools that offer the service for free. At first, the information contained in their digital platforms was verified about the available resources, the analysis settings and the file formats that could be examined. Subsequently, the way in which the tools comparatively evaluated the same text was analyzed, using three paragraphs as models, each one taken from journals on the subject of plagiarism and with different Qualis. Only one tool recognized the three paragraphs as being plagiarized and correctly identifying the original works from which the paragraphs were taken. In the other tools, the three paragraphs were not identified, with some of them being marked as plagiarism in different degrees of similarity, or even as being original, without plagiarism. In this way, the use of plagiarism detection tools must take into account that each one of them accesses a differentiated academic document bank. The denial of plagiarism in a tool does not mean that the document is totally original. It is also necessary to promote greater awareness of the subject in the academic environment, with adequate training in scientific writing, as plagiarism often arises from the difficulty in textual production.